Social Media's Role in the Success of Female Entrepreneurs in Bali's Tourism, Indonesia: An Innovative Marketing - Amanda Bernadette Joana; Anak Agung Ulan Tirta Sari; Elizabeth Furio Perez; Ria Santos Fajilago; Arif Nur Muhammad Ansori (Journal of Strategic Innovation and Business Management, 2025)
The study underscores the profound impact of social media marketing on the brand image and customer engagement of tourism businesses in Bali. Businesses that consistently project a positive and authentic image on social media platforms can foster trust and credibility, leading to increased brand loyalty and repeat business. However, small businesses encounter challenges such as time constraints and lack of technical expertise in implementing effective social media strategies. Outsourcing social media marketing or hiring professionals with the necessary expertise is recommended to address these obstacles. By prioritizing content sharing, brand image building, and customer engagement, small tourism businesses can effectively leverage social media to compete with larger players and reach a broader audience, ultimately enhancing their sales performance and remaining competitive in the evolving landscape of social media marketing.